(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Evaluation of the antimicrobial activity of semisolid formulations of Trachyspermum ammi and Cymbopogon citratus essential oils against five common strains of pathogenic fungi was carried out using the agar well diffusion method. The results indicated that 1 % v/w of T. ammi and C. citratus oils prepared in some bases exhibited remarkable antifungal activity with zone inhibition diameters greater than those for standard antifungal agents. The growth of all five fungal strains was inhibited when T. ammi oil and C. citratus oil were formulated separately in macrogol blend ointment or hydrophilic ointment base. The properties of base into which the oil was incorporated affected its activity. The hydrophilic formulations exhibited higher antifungal activities compared to their lipophilic counterparts and all the formulations were intended for topical use.